AN INTEGRATED METHODOLOGY FOR LAYOUT DESIGN AND WORK ORGANISATION IN A FURNITURE MANUFACTURING PLANT - A. Sutcu; E. Tanritanir; B. Durmusoglu; H.I. Koruca (South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: This study aims to provide an integrated methodology for re-designing the layout and departmental organisation in a job shop environment. While several studies have discussed the specific re-design or re-organisation of small- and medium-sized enterprises (SMEs) through simulation or mathematical models performing improvements, an integrated approach is rare. An integrated simulation-based methodology has been developed for simultaneously re-designing the layout and the departmental organisation of an SME manufacturing facility. A wooden chair manufacturing facility has been used as a case study. It is found that the developed methodology might be useful for other SME manufacturing firms, especially in the furniture industry. AFRIKAANSE OPSOMMING: Hierdie studie hou ‘n geïntegreerde metodologie vir die herontwerp van uitleg en departementele rangskikking in ‘n stukwerkwinkel voor. Terwyl verskeie studies die spesifieke herontwerp en herrangskikking van klein- en mediumgrootte ondernemings deur simulasie en wiskundige modelle probeer verbeter, is ‘n geïntegreerde benadering raar. ‘n Geïntegreerde simulasie-gebaseerde metodologie is ontwikkel en ‘n vervaardigingsaanleg wat houtstoele produseer word as gevallestudie voorgehou. Die toepassing van die model word as nuttig beskou vir ander klein- tot mediumgrootte ondernemings in die meubelbedryf.